Circadian Disruption in Critical Illness - Jobanputra, Aesha M.; Scharf, Matthew T.; Androulakis, Ioannis P.; Sunderram, Jag (Frontiers in Neurology, 2020)
Circadian rhythms play a vital role in metabolic, hormonal, and immunologic function. Circadian rhythms are often disrupted in critically ill patients due to various environmental and patient-related factors. The circadian rhythm modulates the molecular machinery that responds to injury and illness and alteration of the circadian rhythm is associated with deleterious outcomes. Factors contributing to the alteration in circadian rhythmicity in ICU patients include altered light/dark schedules, various feeding protocols and medications. Normalization of circadian rhythmicity in critically ill patients may serve to improve outcomes.